PELAYANAN SOSIAL BERBASIS KELUARGA BAGI ANAK ASUH OLEH YAYASAN SOS CHILDREN’S VILLAGE MEDAN - Irene Simanjuntak (Welfare StatE, 2013)
Children as the future of the nation into the next generation of the ideals of the nation has a right, namely the right to life, the right to grow and develop, the right of protection from discrimination and the right to participation . In growth, children need families. But not all children have a family and not all families are able to provide care for the child. So we need family-based care for children be it in social institutions and foundations that can provide love, shelter and education for children. One of the foundations that implement family-based care is the SOS Children 's Village Medan. Because the authors are interested in this program to conduct research with the title of the family -based analysis of social services for foster children by the SOS Children 's Village Foundation Medan. This study is descriptive and qualitative approach by analyzing family -based social services for foster children by the SOS Children 's Village Foundation Medan. Therefore , the qualitative research is not known and the sample population, but research informants who provide information that is clear, accurate and reliable, both in the form of a statement, information or data that can help meet the problems or issues . This study is divided into two informants, including the key informant foundation staff and key informants that foster children with consideration of age above 12 years as many as 23 foster children. To obtain the required information or data the researchers used the method of data collection through library research and field studies that is by observation, distributing questionnaires and interviews. This study it can be concluded that the SOS Children 's Village has a social service programs based on the family in order to give a sense of compassion that has been missing from the children they are supposed to get from his biological parents or family headliner replaced with foster parents, siblings parenting, aunt and foster care, and to receive educational services and skills, as well as health services with the facilities provided by the foundation. With a family -based services, it is expected the children would grow and flourish like the kids in general. Keywords: Social Services, Social Services Family-Based, Family-Based Social Services For Foster Children